ANALISIS METODE PEMBELAJARAN DARING TERHADAP HASIL BELAJAR SISWA KELAS VIII PADA MATERI SENI RUPA SMP N 24 PADANG - Gadis Lestari; Yahya Yahya (Serupa The Journal of Art Education, 2021)
This study aims to analyze the online learning process and analyze the effectiveness of online learning of grade VIII students at SMP N 24 Padang. This research uses qualitative approach that is descriptive analysis. The collection techniques in this research are literature studies, interviews, observations and documentation. The steps to analyze the data are data collection, display data, data reduction and conclusions/verifying. The results of this study are 1) The online learning process using the Geachool application, the teacher must have a Geschool account first, the Geschool application has a party or admin who collaborates with Google and the admin contracts to the SMP N 24 school. Padang is because at this time the learning process is carried out using the online learning method. After the teacher has an account, the admin explains what features are in the Geschool, namely: Whas's up feature, Gebook feature, Getop feature, Getrol feature, 2) Online learning is still not effective because in the online learning process it is still found. There are many obstacles, ranging from teachers who do not understand and master the application and the application of a teaching model whose features are limited to the very limited understanding of students receiving information from the Geschool given by the teacher. Effectiveness in online learning is something that must be considered in order to maximize student learning outcomes.Keywords: analysis, online learning, student learning outcomes